Impact of servant leadership on organization excellence through employees’ competence: Exploring a cross-cultural perspective - Irfan, Muhammad; Salameh, Anas A.; Saleem, Hina; Tahir Naveed, Rana; Dalain, Ali F.; Shahid, Rao Muhammad (Frontiers in Environmental Science, 2022)
The role of leadership in the organization's parameters has been enhanced, especially in an uncertain environment. New environmental and sustainability laws and social responsibilities are emerging. Corporates are making continuous efforts to be sustainable and excellent in their performance. The purpose of this study is to measure the impact of servant leadership on organizational behavior when work capacity mediates this relationship from a cross-cultural perspective. We created a three-variable survey containing 31 items to collect statistics on 329 employees in the Pakistan, China, and Saudi Arabian corporate sectors. It was a structured, quantitative study. Cross-section procedures have been implemented to gain experience. The conclusions of the study show that employee competence is an intermediary between servant leadership and organizational performance. Servant leaders make a positive difference in an organization's excellence. The article suggests the practical importance of servant leadership and employee competency in the cross-cultural corporate sector. This study influenced the concept of servant leadership in corporate philosophy. Future studies may be directed to finding the relationship through more complex and rigorous research designs.